2020
DOI: 10.3390/insects11060339
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of Five Glutathione S-Transferase Genes and Promoters from Micromelalopha troglodyta (Graeser) (Lepidoptera: Notodontidae) and Their Response to Tannic Acid Stress

Abstract: Plants accumulate phenolic compounds such as tannic acid to resist insect herbivores. The survival of insects exposed to toxic secondary metabolites depends on the detoxification metabolism mediated by limited groups of glutathione S-transferases (GSTs). Micromelalopha troglodyta (Graeser) (Lepidoptera: Notodontidae) is an important foliar pest of poplar trees. GSTs play an important role in xenobiotic detoxification in M. troglodyta. Five GST genes were identified in M. troglodyta and were classified into fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…pipiens larvae. Similar results were observed in Micromelalopha troglodyta in response to tannic acid stress (Tang et al, 2020). Previously, it was reported an induction in GST activity in Cx.…”
Section: Determination Of Metabolic Profilesupporting
confidence: 88%
See 2 more Smart Citations
“…pipiens larvae. Similar results were observed in Micromelalopha troglodyta in response to tannic acid stress (Tang et al, 2020). Previously, it was reported an induction in GST activity in Cx.…”
Section: Determination Of Metabolic Profilesupporting
confidence: 88%
“…GSTs are ubiquitous multifunctional detoxification enzymes that their relationship with the resistance of insects to conventional insecticides was largely investigated (Adeyi et al, 2015). They have been recognized with their important role in xenobiotic detoxification (Tang et al, 2020). Results from the T. stans leaf extract treatment showed an induction of GST activities in Cx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All remaining GST subclasses considered here are cytosolic and unbound [ 51 ]. At least six cytosolic GST subclasses are known in insects—Delta, Epsilon, Sigma, Theta, Omega, and Zeta [ 41 , 42 , 52 ]. Only the Delta and Epsilon subclasses are currently known to confer insecticide resistance [ 53 ]; Delta-type GSTs are observed across all the Insecta, whereas Epsilon-type genes have only been identified in the Holometabola (which contains the Coleoptera) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, esterases could play a decisive role in degradation of sex pheromones of Lepidoptera (Merlin et al ., 2007;Younus et al ., 2014;Baldwin et al ., 2021). Several studies have indicated that plant secondary metabolites impact insect detoxification and their regulating genes (Dermauwet al ., 2013;Giraudo et al ., 2015;Tang et al ., 2020). Likewise, entomoviruses impact the same detoxification enzymes and their corresponding genes (Gui et al ., 2009;Shresthaet al ., 2019;.…”
Section: Introductionmentioning
confidence: 99%